2020
DOI: 10.1186/s13046-020-01550-w
|View full text |Cite
|
Sign up to set email alerts
|

Urinary expression of let-7c cluster as non-invasive tool to assess the risk of disease progression in patients with high grade non-muscle invasive bladder Cancer: a pilot study

Abstract: Background: High grade non-muscle-invasive bladder cancer (HG-NMIBC) is a heterogeneous disease with variable risk of progression. Urinary microRNAs are promising biomarkers for BC detection and surveillance. Let-7c-5p miRNA, clustered with miR-99a-5p and-125b-5p, is deregulated in cancer, including BC. The aim of this study is to evaluate urinary let-7c cluster expression in Ta/T1 HG-NMIBC patients and its impact on progression-free survival (PFS). Methods: Quantitative Real-Time-Polymerase-Chain-Reaction (qR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…These data clearly indicate that patients with low miR‐22 expression in the tumour have high levels of serum miR‐22 and worse clinical outcome, further supporting its role as a non‐invasive biomarker. An opposite miRNA expression profile in biofluids versus matched tumour tissues has already been reported, albeit in other tumours 15,16 . In the context of an onco‐suppressive role of miR‐22, its release from the tumour could suggest a mechanism adopted by cells to reduce the anti‐cancer effect of miR‐22 and maintain their oncogenic potential, as already observed in other cancer models 15,16 .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…These data clearly indicate that patients with low miR‐22 expression in the tumour have high levels of serum miR‐22 and worse clinical outcome, further supporting its role as a non‐invasive biomarker. An opposite miRNA expression profile in biofluids versus matched tumour tissues has already been reported, albeit in other tumours 15,16 . In the context of an onco‐suppressive role of miR‐22, its release from the tumour could suggest a mechanism adopted by cells to reduce the anti‐cancer effect of miR‐22 and maintain their oncogenic potential, as already observed in other cancer models 15,16 .…”
Section: Resultsmentioning
confidence: 63%
“…An opposite miRNA expression profile in biofluids versus matched tumour tissues has already been reported, albeit in other tumours. 15,16 In the context of an onco-suppressive role of miR-22, its release from the tumour could suggest a mechanism adopted by cells to reduce the anti-cancer effect of miR-22 and maintain their oncogenic potential, as already observed in other cancer models. 15,16 These observations might reflect a yet undefined molecular mechanism of selective miRNA release into the extracellular environment.…”
Section: Resultsmentioning
confidence: 84%
“…For example, Sebastian L Hofbauer et al identified a 6-microRNA signature in urine for diagnosis of bladder cancer (21) and Wataru Usuba et al identified a 7-miRNA panel in serum for specific and early detection in bladder cancer (22). In terms of prognosis research, the study found that let-7c cluster evaluation may enhance prognosis by recognizing patients' risk of progression and addressing early radical therapy in high grade non-muscleinvasive bladder cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Previously investigated prognostic and predictive blood-based biomarkers in patients treated with RC for UC either do not offer a clinically meaningfully discriminative ability and/or lack external validation. [8][9][10][11][12][13][14][15][16] IGF-I is produced by liver cells, 17 tumor cells, and cancerassociated macrophages. 17 The IGF-I signaling pathway, including IGF-I itself, the circulating levels of IGFBPs, and its tissue receptors (IGF-IR) have been found to promote tumor cell proliferation, metastasis, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologic variables such as T stage and lymph node status remain the most important prognostic markers after RC 6,7 . Previously investigated prognostic and predictive blood‐based biomarkers in patients treated with RC for UC either do not offer a clinically meaningfully discriminative ability and/or lack external validation 8–16 …”
Section: Introductionmentioning
confidence: 99%